Coated fertilizer, preparation method and application thereof

By using non-toxic, biodegradable ingredients and natural polymers to prepare enveloped fertilizers, the problems of high cost and poor biodegradability of existing controlled release fertilizer materials are solved, and efficient and environmentally friendly controlled release effects of fertilizers are achieved.

CN119403776APending Publication Date: 2025-02-07UPM KYMMENE OYJ

Patent Information

Application Number
CN202380047955.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing controlled release fertilizer materials have high cost, poor biodegradability and potential toxicity, making it difficult to meet the agricultural demand for efficient and environmentally friendly fertilizers.

Method used

The coating fertilizer is prepared using non-toxic, biodegradable ingredients and natural polymers. The coating includes the inner layer of lignin and the hydrophobic outer layer. Through the combination of bio-based polymers and plasticizers, a controlled release coating is formed. structure.

Benefits of technology

It realizes effective controlled release of fertilizers, extends the controlled release period, improves the release rate and stability, and avoids microplastic residues and the use of organic solvents, meeting environmentally friendly and efficient agricultural needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403776A_ABST
    Figure CN119403776A_ABST
Patent Text Reader

Abstract

The present disclosure relates to a controlled release coated fertilizer product comprising a core of fertilizer particles and a coating of a readily biodegradable component and a natural polymer. The envelope comprises an inner layer comprising lignin and a hydrophobic outer layer. The present disclosure also relates to a method of making a coated fertilizer product, and the use of the coated fertilizer for controlled release of nutrients in agriculture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a controlled release coated fertilizer product, which includes a fertilizer particle core and a coating of a biodegradable component and a natural polymer. The coating includes an inner layer containing lignin and a hydrophobic outer layer. In particular, the present disclosure relates to a coated fertilizer product, wherein the lignin of the inner coating is captured in a biodegradable bio-based polymer. The present disclosure also relates to a method for preparing the coated fertilizer product, and the use of the coated fertilizer for nutrient controlled release in agriculture. Background Art

[0002] The growth of the global population has led to an increase in food production. This means that the agricultural sector is bound to use large amounts of fertilizers in food production, which will further exacerbate harmful gas emissions and eutrophication of water bodies associated with fertilizer use. These factors, coupled with the limited availability of arable land, are using controlled release fertilizers (CRFs) to increase crop yields (by reducing nitrogen volatilization and leaching losses) while limiting environmental pollution caused by the use of large amounts of fertilizers.

[0003] As the name implies, CRF allows for the controlled release of nutrients into plants, usually by coating water-soluble fertilizer particles with a protective (semi-permeable, semi-impermeable, or water-insoluble) membrane. Several polymers have been used as coating materials for fertilizers, however, the cost, biodegradability, and toxicity of these materials have been major drawbacks in their use. To overcome these challenges, the use of renewable and bio-based resources such as natural polymers and biodegradable synthetic polymers is gaining attention. Among these natural polymers, lignin, along with cellulose and hemicellulose, is the main component of plant cells, and lignin is the second most abundant biopolymer after cellulose.

[0004] Currently, the paper industry and biorefineries are the two main sources of lignin. Kraft pulp mills produce about 70 million tons of lignin each year. Most of the lignin is used as fuel to run the mills. The global production of unused kraft lignin as fuel is about 100,000 tons, while the production of sulfur-free lignin is less than 5,000 tons. Lignin has attracted interest in the materials field due to its low cost, non-toxicity, diverse functional groups, renewability and degradability. However, its large-scale application has been limited due to its complex structure.

[0005] Although processes for producing controlled-release fertilizers, particularly from natural or biodegradable polymers, have been under research and development, there are still challenges associated with producing controlled-release fertilizers using bio-based resources that need to be overcome. Summary of the invention

[0006] An object of the present disclosure is to provide a controlled-release coated fertilizer product and a method for preparing the controlled-release coated fertilizer.

[0007] The objects of the present disclosure are achieved by products, methods and uses as characterized by the independent claims. Preferred embodiments of the present disclosure are disclosed in the dependent claims.

[0008] The present disclosure is based on the concept of providing a coated fertilizer product and a method for preparing the coated fertilizer, wherein the fertilizer coating comprises an inner layer comprising lignin and a hydrophobic outer layer.

[0009] In more detail, the present disclosure is based on the idea of ​​providing a coating consisting entirely of non-toxic, readily biodegradable components and / or natural polymers. This means that the coating contains no organic solvents, no non-biodegradable copolymers containing microplastics are used, and the lignin itself is not chemically modified.

[0010] One advantage of the products, methods and uses of the present disclosure is that since no plastic-like non-biodegradable polymers are used, no microplastics from the biodegradable coating will remain in the soil after the fertilizer is dissolved.

[0011] Furthermore, since no organic solvents are used and the bio-based polymer, plasticizer and optional stabilizer and / or thickener are preferably water-soluble, another advantage of the products, methods and uses of the present disclosure is easier drying and film coating.

[0012] Another advantage of the products, methods and uses of the present disclosure is improved controlled release of fertilizer products.Preferably, the controlled release period, release rate (conductivity over time) and weight loss of the controlled release fertilizer product are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] The present disclosure will be described in more detail below through preferred embodiments with reference to the accompanying drawings, in which:

[0014] Figure 1 shows the change in release rate (conductivity) over time of the coated fertilizers according to the present disclosure and comparative examples; and

[0015] Figure 2 The release rate (weight loss) of the coated fertilizers according to the present disclosure and comparative examples is shown as a function of time. DETAILED DESCRIPTION

[0016] The present disclosure relates to a coated fertilizer product, wherein the coated fertilizer product comprises a fertilizer particle core and a coating of a readily biodegradable component and / or a natural polymer, and wherein the coating comprises an inner layer comprising lignin and a hydrophobic outer layer.

[0017] The coated fertilizer product of the present disclosure and the coated fertilizer obtained by the method of the present disclosure are coated fertilizer products for controlled release of fertilizer. Generally, the controlled release period of the coated fertilizer product exceeds 4 days, preferably exceeds 30 days, more preferably exceeds 3 months, and most preferably exceeds 6 months.

[0018] The present disclosure also relates to a method for preparing a coated fertilizer, wherein the fertilizer has a coating of a biodegradable component and / or a natural polymer, and wherein the method comprises coating the fertilizer particles with a coating dispersion comprising lignin, a bio-based polymer and a plasticizer to provide an inner coating layer and obtain a single-layer coated fertilizer, which is then coated with a hydrophobic outer layer. The bio-based polymer and the plasticizer are biodegradable. The coated fertilizer is thereby obtained.

[0019] The present disclosure also relates to the use of the coated fertilizer product or the coated fertilizer prepared by the method for controlled nutrient release and as a soil conditioner in agriculture, preferably in turf, crop cultivation, greenhouse cultivation and / or ornamental gardening. The coated fertilizer product or the coated fertilizer prepared by the method is applied by topdressing on the soil or mixing the fertilizer into the soil before sowing.

[0020] In the context of this specification, the term "lignin" refers to lignin from any suitable lignin source. The term "unchemically modified lignin" refers to lignin that has not been chemically modified after lignin extraction. In general, lignin can be divided into three major categories: softwood, hardwood and annual plants. Lignin is a complex polymer with different chemical structures even in the same species. It consists of three phenylpropane units, of which p-hydroxyphenyl alcohol (H), guaiacol (G) and syringol (S) are the main precursors (single lignin monomers), which are heterogeneously connected to each other through several types of CC and CO bonds. Ether bonds account for 60-70% of the bonds between phenylpropane units, of which the most common is β-O-4 bonds. But there are also other types of bonds, such as α-O-4 or CC bonds. For the latter, there are mainly 5-5, β-5 or β-β' bonds. Lignin contains many functional groups, some of which are conjugated, which can absorb ultraviolet rays and thus give wood color. On average, softwoods have a higher lignin content than hardwoods. Softwood has a higher proportion of guaiacol in its lignin, while hardwood has mostly syringol. This has an effect on the chemical groups in the lignin. Thus, softwood has more hydroxyl groups, while hardwood has more methoxyl groups.

[0021] In some embodiments of the invention, lignin is substantially pure lignin. The term "substantially pure lignin" is understood to be at least 70% pure lignin, or at least 90% pure lignin, or at least 95% pure lignin, or at least 98% pure lignin. Substantially pure lignin may contain up to 30%, or up to 10%, or up to 5%, or up to 2% other components and / or impurities. Extracts and carbohydrates (such as hemicellulose) may be examples of such other components.

[0022] Typically, the carbohydrate content in lignin is less than 30% by weight, or less than 10% by weight, or less than 5% by weight, or less than 3% by weight, or less than 2.5% by weight, or less than 2% by weight. The carbohydrate content present in lignin can be measured by high performance anion exchange chromatography with a pulsed amperometric detector (HPAE-PAD) according to the SCAN-CM71 standard.

[0023] The ash percentage of lignin is usually less than 7.5% by weight, or less than 5% by weight, or less than 3% by weight, or less than 1.5% by weight. The ash content can be determined as follows: First, the dry solid content of the sample is measured in an oven at 105°C for 3 hours. The ceramic crucible is preheated to 700°C for 1 hour and weighed after cooling. The sample (1.5g-2.5g) is placed in a ceramic crucible and weighed. The crucible with a mouth is placed in a cold oven. The oven temperature is increased: 20-200°C for 30 minutes => 200-600°C for 60 minutes => 600-700°C for 60 minutes. Continue to burn at 700°C for 60 minutes without covering. Cool the crucible in a desiccator, drip a few drops of hydrogen peroxide (H2O2, 30%) into the sample, and then burn it in an oven at 700°C for 30 minutes. If there are still black spots in the ash, repeat the hydrogen peroxide treatment and combustion. The crucible was cooled and weighed. All weighings were performed after cooling in a desiccator with an accuracy of 0.1 mg.

[0024] Result calculation

[0025] Ash content % = (100a x 100) / (b x c)

[0026] in

[0027] a=ash weight, g

[0028] b = sample weight, g

[0029] c = dry solids of sample, %.

[0030] The ash content of a sample is the mass of the sample remaining after combustion and annealing, expressed as a percentage of the dry content of the sample.

[0031] In some embodiments of the invention, the lignin is industrial lignin. In the context of this specification, the term "industrial lignin" refers to lignin derived from lignin in any biomass by any technological process. In one embodiment, industrial lignin refers to lignin obtained from an industrial process.

[0032] The lignin used to prepare the coating dispersion is generally selected from the group consisting of kraft lignin, steam explosion lignin, biorefining lignin, supercritical separation lignin, hydrolysis lignin, flash precipitation lignin, biomass source lignin, lignin from alkaline pulping process, lignin from soda process, lignin from organic solvent pulping, lignin from alkali process, lignin from enzyme hydrolysis process, and any combination thereof. In one embodiment, the lignin is wood-based lignin. The lignin can be derived from softwood, hardwood, annual plant, or any combination thereof, and typically the lignin is not chemically modified after extraction.

[0033] In this specification, the term "flash precipitated lignin" is understood to mean lignin precipitated from the black liquor by using a carbon dioxide-based acidulant (preferably carbon dioxide) in a continuous process, under the influence of an overpressure of 200-1000 kPa, reducing the pH of the black liquor stream to the precipitation level of lignin, and then suddenly releasing the pressure of the precipitated lignin. The method for producing flash precipitated lignin has been disclosed in patent application FI20106073. The residence time of the above method is less than 300s. The particle size of the flash precipitated lignin particles is less than 2 microns, forming agglomerates, which can be separated from the black liquor by filtration and the like. Compared with ordinary kraft lignin, the advantage of flash precipitated lignin is that it is more reactive. The flash precipitated lignin can be purified and / or activated as needed for further processing.

[0034] Lignin can be derived from an alkaline process. The alkaline process can first liquefy the biomass with a strong base and then perform a neutralization process. After the alkaline treatment, the lignin can be precipitated in a similar manner as described above.

[0035] Lignin can be derived from steam explosion, a pulping and extraction technique that can be applied to wood and other fibrous organic materials.

[0036] In this specification, unless otherwise stated, "biorefinery lignin" is understood to mean lignin that can be recovered from a refinery facility or process that converts biomass into fuels, chemicals and other materials.

[0037] In this specification, unless otherwise specified, "supercritically separated lignin" is understood to be lignin that can be recovered from biomass using supercritical fluid separation or extraction techniques. Supercritical conditions correspond to temperatures and pressures that exceed the critical point of a given substance. Under supercritical conditions, there are no separate liquid and gas phases. Supercritical water or liquid extraction is a method of using water or liquids to decompose and convert biomass into cellulosic sugars under supercritical conditions. The water or liquid acts as a solvent to extract sugars from cellulosic plant matter, while the lignin remains as solid particles.

[0038] Lignin can be derived from a hydrolysis process. Lignin derived from a hydrolysis process can be recovered from pulp or wood chemical processes.

[0039] Lignin can be derived from an organosolv process, which is a pulping technology that uses organic solvents to dissolve lignin and hemicellulose.

[0040] In some embodiments of the present disclosure, the lignin consists of kraft lignin (such as softwood kraft lignin). In one embodiment, the lignin is softwood kraft lignin. In some embodiments of the present disclosure, the lignin is a combination of softwood lignin and hardwood lignin, typically lignin from hardwood is at most 30 wt%, or at most 25 wt%, or at most 10 wt%, or at most 5 wt%. In some embodiments of the present disclosure, the lignin consists of EH lignin and / or the lignin is EH lignin derived from hardwood.

[0041] Unless otherwise specified, "kraft lignin" in this specification is understood to be lignin derived from kraft black liquor. Black liquor is an alkaline aqueous solution of lignin residues, hemicellulose and inorganic chemicals used in the kraft pulping process. The black liquor from the pulping process includes components derived from different softwood and hardwood species in different proportions. Lignin can be separated from the black liquor by different techniques such as precipitation and filtration. Lignin usually begins to precipitate when the pH value is lower than 11-12. Different pH values ​​can be used to precipitate lignin parts with different properties. These lignin parts differ from each other in molecular weight distribution (such as Mw and Mn), polydispersity, hemicellulose and extract content. The molar mass of lignin precipitated at a higher pH value is higher than the molar mass of lignin precipitated at a lower pH value. In addition, the molecular weight distribution of the lignin part precipitated at a lower pH value is broader than the molecular weight distribution of the lignin part precipitated at a higher pH value. The precipitated lignin can be purified from inorganic impurities, hemicellulose and wood extractives by an acid washing step. Further purification can be achieved by filtration.

[0042] In this specification, the term "enzymatic lignin" (EH) is understood to mean lignin from an enzymatic hydrolysis of lignocellulosic biomass. In the enzymatic hydrolysis process, cellulose is hydrolyzed by enzymes into carbohydrates, and the unhydrolyzed solid residue comprises lignin. If necessary, the lignin can be purified. The EH lignin isolated from pure biomass is substantially free of sulfur (less than 3% sulfur). Preferably, the biomass is pretreated to remove hemicellulose before the cellulose is hydrolyzed.

[0043] In the present specification, the term "dispersion" is understood as a dispersion formed by dispersing lignin in water when preparing the coating dispersion of the present disclosure.

[0044] In this specification, the term “readily biodegradable” is to be understood as a compound presumed to be biodegradable, i.e. rapidly and ultimately biodegraded (“mineralized”) in the environment. If a compound is considered to be readily biodegradable, no further investigation is required on the possible impacts of the chemical itself or its transformation products on the environment. In other words, a compound presumed to be biodegradable is considered to be biodegradable by screening tests (e.g. OECD TG 2017 / 1100 for an extended duration of up to 60 days, based on the Annex to Background Document to the Opinion on the Annex XV dossier proposing restrictions on intentionally added microplastics of December 2020 (Committee for Risk Assessment (RAC), Committee for Socio-economic Analysis (SEAC))). Compounds of 301B, C, D, F, and 310) are not considered to pose a serious challenge to the metabolic capacity of aerobic aquatic environments and are considered to be readily degradable in practical environments. In addition, while some natural polymers (such as lignin) fail all tests of the biodegradability criteria, natural polymers that have not been chemically modified are considered exceptions, so lignin itself is considered to meet the biodegradability criteria. Typically, lignin biodegrades slowly in water and soil (80-98% by weight with a half-life of 1 month to 1 year). For example, kraft lignin and other "isolated lignins" are also considered natural polymers, as long as the lignin is not further chemically modified after being isolated using different extraction processes.

[0045] In this specification, the term "hydrophobic outer layer" is understood to be the outermost layer of the coated fertilizer product, whose surface is waterproof. The term "hydrophobic" means that the surface has water-repellent and anti-wetting properties. In addition, in general, hydrophobic means that the hydrophobic surface is a low-energy surface that repels water. Hydrophobic molecules are generally non-polar, which means that the atoms that make up the molecule do not generate an electrostatic field. Test methods for detecting the presence of a hydrophobic (non-wetting) film on a surface include visual (appearance), contact angle (static, dip-coated on a glass slide), immersion (increased and reduced temperatures), temperature and humidity exposure, corrosion resistance to salt spray / fog, refractive index, glass transition temperature (Tg), thermal stability, dielectric strength, dielectric constant, dissipation factor, solder penetration ability, UV exposure, and moisture and insulation resistance (MIR).

[0046] In an embodiment of the present disclosure, the coating of the coated fertilizer product and the coating of the coated fertilizer prepared according to the method of the present disclosure are composed of readily biodegradable components and / or natural polymers. This should be understood in this specification as being free of microplastics and organic solvents.

[0047] In this specification, the term "controlled release fertilizer" is understood to mean a granular fertilizer that gradually releases nutrients into the soil (eg, over a controlled release period). Controlled release fertilizers are also called slow release fertilizers.

[0048] In an embodiment of the present disclosure, the coating of the coated fertilizer product and the coating of the coated fertilizer prepared according to the disclosed method have an inner layer comprising lignin. Typically, the first inner layer also comprises at least one other biodegradable bio-based polymer (non-lignin) and / or a biodegradable plasticizer. Optionally, the inner layer also comprises one or more substances, such as natural gum, preferably xanthan gum or gellan gum, as a stabilizer and / or thickener. In an embodiment of the present disclosure, the bio-based polymer is generally cross-linked around the inner layer lignin, and the lignin is captured or embedded in the bio-based polymer. Preferably, the bio-based polymer and / or the plasticizer are water-soluble.

[0049] In an embodiment of the present disclosure, the coating of the coated fertilizer product and the coating of the coated fertilizer prepared according to the method of the present disclosure, in addition to the inner layer, also includes at least one other layer, which is a hydrophobic outer layer, preferably, the hydrophobic outer layer is the outermost layer. Typically, the hydrophobic outer layer is an esterified fatty acid, suberin or wax, preferably selected from non-combustible oils, suberin or wax, more preferably the wax is selected from carnauba wax, biowax (80-130), rice bran wax and candelilla wax, and most preferably the wax is carnauba wax.

[0050] In an embodiment of the present disclosure, a coated fertilizer product including a fertilizer particle core and a coating is provided. The coating includes an inner layer, which includes lignin, at least one other bio-based polymer and a plasticizer. The coating also includes a hydrophobic and waterproof outer layer. The coating of the present disclosure does not contain an organic solvent, and the bio-based polymer and the plasticizer are biodegradable. The lignin is usually not chemically modified, and the outer layer usually includes esterified fatty acids, suberin and / or wax. Generally, biodegradable bio-based polymers and / or plasticizers are compounds that do not contain microplastics and can pass biodegradability screening tests (e.g., according to the background document annex to the Annex XV file in December 2020 on the restriction of intentionally added microplastics (Risk Assessment Committee (RAC), Socio-Economic Analysis Committee (SEAC)), OECD TG 301B, C, D, F and 310 for a duration of up to 60 days), and are natural polymers or natural polymers that have not been chemically modified.

[0051] In a preferred embodiment of the present disclosure, the coating of the coated fertilizer product and the coating of the coated fertilizer prepared according to the method of the present disclosure comprises at least two different layers, preferably, the two-layer coating is obtained by a two-layer process according to the method of the present disclosure.

[0052] In an embodiment of the present disclosure, the coating of the coated fertilizer product and the coating of the coated fertilizer prepared according to the method of the present disclosure account for 1-25% by weight of the total weight of the coated fertilizer product, preferably 5-20% by weight of the total weight of the coated fertilizer product, more preferably 8-16% by weight, including the amount of the coating between the following two amounts: 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24 and 25% by weight of the total weight of the coated fertilizer product. The thickness measured with a scanning electron microscope (SEM) is generally 20 to 225 μm. The thickness varies depending on the shape of the specific particles because typical fertilizer particles are not perfectly spherical. Generally, the performance will improve as the coating thickness increases. Generally, the portion formed by the hydrophobic outer layer accounts for a smaller (weight %) and / or thinner (μm) portion in the coating.

[0053] In an embodiment of the present disclosure, a method for preparing a coated fertilizer comprises:

[0054] a) providing a coating dispersion comprising lignin, at least one other bio-based polymer and a plasticizer, wherein the lignin is not chemically modified and the bio-based polymer and the plasticizer are biodegradable;

[0055] b) coating the fertilizer particles with a coating dispersion to provide a coating inner layer and obtain a single-layer coated fertilizer;

[0056] c) coating the single-layer coated fertilizer with an outer layer, and

[0057] d) obtaining coated fertilizers,

[0058] And wherein no organic solvent is used in the coating. Typically, the outer layer is hydrophobic.

[0059] In an embodiment of the present disclosure, the coating dispersion is prepared from a mixture comprising at least lignin, a bio-based polymer, a plasticizer and water, wherein the bio-based polymer and the plasticizer are biodegradable. Typically, the coating dispersion is prepared by heating the mixture comprising lignin, a bio-based polymer, a plasticizer and water to 70 to 120° C., or heating the water to 70 to 120° C., and then adding the mixture comprising lignin, a bio-based polymer and a plasticizer. The lignin particles will not dissolve, but will be dispersed into the mixture. Preferably, the amount of lignin is 5 to 15% by weight of the coating dispersion, preferably 8-10% by weight; the amount of the bio-based polymer is 1 to 10% by weight of the coating dispersion, preferably 3-5% by weight; the amount of the plasticizer is 0.5 to 5% by weight of the coating dispersion, preferably 0.5-2.5% by weight; the amount of water is 70 to 93.5% by weight of the coating dispersion, preferably 77.5-86% by weight. Optionally, the mixture also comprises a stabilizer and / or a thickener, such as a natural gum, preferably gellan gum or xanthan gum, preferably in an amount of 0.001-0.005 wt %, preferably 0.0025-0.005 wt %. Typically, the temperature is the boiling point of water, and the temperature depends on the pressure. For example, the pressure is 2 bar and the temperature is 120° C. Preferably, any conventional mixer or agitator is used to stir the mixture for 10 minutes to 2 hours, preferably 10 to 60 minutes, more preferably 10 to 40 minutes, and most preferably 15 to 35 minutes to prepare the coating dispersion.

[0060] In an embodiment of the present disclosure, the hydrophobic outer layer is generally an esterified fatty acid, suberin or a wax emulsion, preferably selected from non-combustible oils, suberin or a wax emulsion, more preferably the wax of the wax emulsion is selected from carnauba wax, biowax (80-130), rice bran wax and candelilla wax, most preferably the wax is carnauba wax.

[0061] In embodiments of the present disclosure, the coating dispersion is typically applied in an amount of 0.1 to 1, preferably 0.3 to 0.7 weight percent compared to the fertilizer. The compound for the hydrophobic outer layer (preferably a wax emulsion) is typically applied in an amount of 0.05 to 1, preferably 0.1 to 0.25 weight percent.

[0062] In the embodiments of the present disclosure, the fertilizer granules are typical commercial products, usually multi-nutrient granular fertilizers, wherein each granule contains the nutrient ratio required for a specific use. Typically, fertilizers contain nitrogen, phosphorus, and potassium compounds that are essential for plant growth.

[0063] In the embodiments of the present disclosure, coating is generally performed by spray coating, preferably drum coating, turning pan coating or fluidized bed coating, more preferably fluidized bed coating.

[0064] In an embodiment of the present disclosure, the biodegradable bio-based polymer used for the coated fertilizer product and the coated fertilizer prepared according to the method of the present disclosure is generally selected from the group consisting of polyvinyl alcohol (PVOH), polybutylene succinate (PBS), polyhexamethylene succinate (PHS), polyglycolide (PGA), polyhydroxyalkanoate (PHA), polylactic acid (PLA), polycaprolactone Capa and polybutylene terephthalate-adipate (PBAT), preferably PVOH.

[0065] In embodiments of the present disclosure, biodegradable plasticizers for coated fertilizer products and coated fertilizers prepared according to the disclosed methods help keep the mixture in dispersion form. The biodegradable plasticizer is typically selected from the group consisting of polyethylene glycol (PEG), propylene carbonate, epoxidized cardanol, acetylated castor oil, epoxy soy acid methyl ester, dibutyl phthalate, and triethyl citrate, preferably polyethylene glycol 6000 (PEG 6000).

[0066] In an embodiment of the present disclosure, the coated fertilizer product and the coated fertilizer prepared according to the method of the present disclosure are controlled release fertilizer products. Preferably, the controlled release period of the controlled release fertilizer product exceeds 4 days, preferably exceeds 30 days, more preferably exceeds 3 months, and most preferably exceeds 6 months. Typically, the controlled release fertilizer product has a release rate of less than 8 mS / cm, preferably less than 6 mS / cm, and more preferably less than 4 mS / cm after 96 hours at 23°C and 50% relative humidity. Typically, the weight loss of the controlled release fertilizer product after 96 hours is less than 40% by weight of the total dry matter, preferably less than 20% by weight, more preferably less than 18% by weight, and most preferably less than 15% by weight.

[0067] Example

[0068] Example 1 Preparation of lignin coating

[0069] The preparation of the formulation was carried out using a one-pot method.

[0070] Appropriate amounts of lignin (KL, kraft lignin powder (80-98 wt%), pH 2.5-4.5 (10% solution) or EH, enzymatic hydrolyzed lignin), PEG 6000 (solubility = 1.2 g / mL at 20°C; biodegradability aerobic - exposure time 28 days, result: 74.85% - readily biodegradable. (OECD Test Guide 301D)), PVOH (Exceval, biodegradable, purity >94%; solubility = 10-99%), xanthan gum and optional wax (anionic carnauba wax) are mixed and dried, then added to excess water at 100°C with constant stirring. The weight ratio of lignin, PEG, and PVOH is 1:0.25:0.5 (200g:50g:100g). In addition, xanthan gum was added in a ratio of 0.025 (EHNM (15), and EHNM + CW) or 0.05 (KLNM_2X (15) and KLNM_2X + CW), and wax was added in a ratio of 0.5 to some mixtures (EHNM + CW and KLNM_2X + CW). Excess water was about 100 g to compensate for evaporation during mixing. Stirring continued for about 30 minutes to ensure dissolution of soluble compounds and formation of a homogeneous mixture.

[0071] Table 1 lists the characteristics of coated and coated fertilizers.

[0072] Table 1. Characteristics of coated and coated fertilizers

[0073]

[0074] The envelope of Table 1 has the following characteristics:

[0075] CW_1 = Single layer coating, containing only wax

[0076] EHNM (15) = single layer coating, containing enzymes that hydrolyze lignin

[0077] KLNM_2X(15) = Single layer coating, containing kraft lignin

[0078] EHNM+CW=single layer coating, including enzyme hydrolysis of lignin and wax

[0079] KLNM_2X+CW = single layer film, containing kraft lignin and wax

[0080] CW_KLNM_2X = two layers of coating: inner layer KLNM_2X, outer layer wax

[0081] CW_EHNM(15) = two layers of coating: inner layer of EHNM(15), outer layer of wax

[0082] The coating dispersion was fed into a fluidized bed coating machine (Neuhaus Neotec Laboratory Fluidized Bed Center LFB) for coating of the fertilizer granules.

[0083] The fertilizer granules used in the examples are commercial multi-nutrient fertilizer granules.

[0084] A 10 wt% anionic carnauba wax emulsion [solid content 25%; pH = 10; viscosity (23°C) = 150 mPa.s] was fed into a fluidized bed coating machine (Neuhaus Neotec Laboratory Fluidized Bed Center LFB) to coat the fertilizer particles that had been coated with a coating dispersion containing lignin (EHNM (15) and KLNM_2x (15)) to achieve a two-step coating.

[0085] Slow-release behavior in H2O

[0086] 1 g of uncoated fertilizer granules (REF) and fertilizer granules with different coatings were placed in 100 mL of H2O to analyze the slow release behavior of the coating. The samples were stored in a room at a temperature of 23°C and a relative humidity of 50%. The controlled release was evaluated by the water dissolution method. The conductivity of the granule-H2O solution was measured according to standard SFS-EN27888 (1994). The weight loss was calculated within 4 days by removing the liquid and drying the solid at 60°C for 12 hours and then weighing it.

[0087] Figure 1 The conductivity changes over time after immersion in water for 4 days (96 hours) are shown for the selected samples. The release rates of the two-step coated granules (named CW_KLNM_2X and CW_EHNM(15)) were compared with those of the uncoated fertilizer sample (named REF), the wax-free monolayer coating (named EHNM(15) and KLNM_2x(15)), the monolayer coating containing the wax mixture (named EHNM+CW and KLNM_2X+CW), the monolayer coating containing only wax (named CW_1), and the commercial polyethylene fertilizer coating (named Poligen).

[0088] from Figure 1As can be seen, the release rates (conductivity changes over time) of the two-step coatings (CW_KLNM_2X and CW_EHNM(15)) show a significant improvement in the ion release rate of the fertilizer granules compared to the reference sample and any single-layer coating. The release rate of the single-layer coating did not decrease significantly. The release rate of the single-layer coating containing EH or KL lignin (EHNM(15) and KLNM_2x(15)) or a mixture of KL or EH lignin and carnauba wax (EHNM+CW and KLNM_2X+CW) was only slightly improved compared to the uncoated reference fertilizer (REF). After 24 hours, the release rate of wax only (CW_1) was also comparable to that of the other single-layer coated fertilizers. The results of the double-layer coating are comparable to those of commercial-grade polyethylene fertilizer coatings (Poligen).

[0089] Figure 2 The relative dry matter remaining after soaking some samples in water for 4 days (96 hours) is shown. The weight loss of the coated fertilizers is consistent with the conductivity measurements.

[0090] ICP-MS (Inductively Coupled Plasma Mass Spectrometry) was used to identify the ions present in the solution. As can be seen in Table 2, the ICP-MS results for potassium and phosphorus correlated particularly well with the results of the conductivity and weight loss measurements.

[0091] Table 2. Ion content of selected coating samples

[0092]

[0093] Further testing (not mentioned above) showed that the conductivity of the sample having a first layer of wax and a second layer of coating dispersion comprising lignin was consistent with a single layer coating of wax only.

[0094] Morphology and thickness analysis

[0095] Morphological analysis was performed using scanning electron microscopy (SEM) and stereomicroscopy. The thickness of the coating layer was estimated using SEM. Three particles were randomly selected and morphologically analyzed using SEM and stereomicroscopy. A rough estimate of the thickness was obtained by cutting the particles in half, fixing them on a support, and analyzing them using SEM.

[0096] The thickness of the single-layer coating containing wax varied between 86 μm and 132 μm, and the coating thickness of the double-layer coating varied between 102 μm and 142 μm.

Claims

1. A coated fertilizer product, comprising a fertilizer particle core and a coating, characterized in that: The coating comprises an inner layer and an outer layer, the inner layer comprising lignin, a bio-based polymer, and a plasticizer, wherein the coating is free of organic solvents, wherein the bio-based polymer and the plasticizer are biodegradable, wherein the lignin is not chemically modified, and wherein the outer layer is hydrophobic.

2. The product according to claim 1, characterized in that The coated fertilizer product is a controlled-release fertilizer product. Preferably, the controlled-release period of the coated fertilizer product is more than 4 days, preferably more than 30 days, more preferably more than 3 months, and most preferably more than 6 months.

3. A product according to any one of the preceding claims, characterized in that The bio-based polymer forms cross-links around the lignin in the inner layer.

4. A product according to any one of the preceding claims, characterised in that The bio-based polymer is water soluble.

5. A product according to any one of the preceding claims, characterised in that The plasticizer is water soluble.

6. A product according to any one of the preceding claims, characterised in that The outer layer is esterified fatty acid, suberin or wax, preferably selected from non-combustible oils, suberin or wax, more preferably the wax is selected from carnauba wax, rice wax and candelilla wax, most preferably the wax is carnauba wax.

7. A product according to any one of the preceding claims, characterised in that The coating accounts for 1-25% by weight of the total weight of the coated fertilizer product, preferably 5-20% by weight, and more preferably 8-16% by weight.

8. A product according to any one of the preceding claims, characterised in that The controlled-release fertilizer product has a release rate of less than 8 mS / cm, preferably less than 6 mS / cm, and more preferably less than 4 mS / cm, after 96 hours at 23°C and 50% relative humidity.

9. A product according to any one of the preceding claims, characterised in that The weight loss of the coated fertilizer product after 96 hours is less than 40 wt %, preferably less than 20 wt %, more preferably less than 18 wt %, most preferably less than 15 wt % of the total dry matter.

10. A method for preparing coated fertilizer, characterized in that: The method comprises: a) providing a coating dispersion comprising lignin, a bio-based polymer and a plasticizer, wherein the lignin is not chemically modified and the bio-based polymer and the plasticizer are biodegradable; b) coating the fertilizer particles with a coating dispersion to provide a coating inner layer and obtain a single-layer coated fertilizer; c) coating the single-layer coated fertilizer with an outer layer, wherein the outer layer is hydrophobic, and d) obtaining coated fertilizers, No organic solvent is used.

11. The method according to claim 10, characterized in that The coating dispersion is prepared by heating a mixture comprising lignin, a bio-based polymer, a plasticizer and water to 70 to 120° C., or heating water to 70 to 120° C. and then adding a mixture comprising lignin, a bio-based polymer, a plasticizer and optionally a stabilizer and / or a thickener.

12. The method according to claim 11, characterized in that The mixture is mixed for 10 minutes to 2 hours, preferably 10 to 60 minutes, more preferably 10 to 40 minutes, most preferably 15 to 35 minutes.

13. The method according to any one of claims 11 or 12, characterized in that The amount of lignin is 5 to 15% by weight of the coating dispersion, preferably 8-10% by weight; the amount of bio-based polymer is 1 to 10% by weight of the coating dispersion, preferably 3-5% by weight; the amount of plasticizer is 0.5 to 5% by weight of the coating dispersion, preferably 0.5-2.5% by weight; the amount of water is 70 to 93.5% by weight of the coating dispersion, preferably 77.5-86% by weight.

14. The method according to any one of claims 10 to 13, characterized in that The coating is spray coating, preferably roller coating, tumbler coating or fluidized bed coating, more preferably fluidized bed coating.

15. The method according to any one of claims 10 to 14, characterized in that The outer layer is esterified fatty acid, suberin or wax emulsion, preferably selected from non-combustible oil, suberin or wax emulsion, more preferably the wax of the wax emulsion is selected from carnauba wax, biowax (80-130), rice bran wax and candelilla wax, most preferably the wax is carnauba wax.

16. The product according to any one of claims 1 to 9 or the method according to any one of claims 10 to 15, characterized in that The bio-based polymer is selected from the group consisting of polyvinyl alcohol (PVOH), polybutylene succinate (PBS), polyhexamethylene succinate (PHS), polyglycolide (PGA), polyhydroxyalkanoate (PHA), polylactic acid (PLA), polycaprolactone Capa and polybutylene terephthalate-adipate (PBAT), preferably PVOH.

17. The product according to any one of claims 1 to 9 or the method according to any one of claims 10 to 15, characterized in that The plasticizer is selected from the group consisting of polyethylene glycol (PEG), propylene carbonate, epoxidized cardanol, acetylated castor oil, epoxy soy acid methyl ester, dibutyl phthalate and triethyl citrate, preferably polyethylene glycol 6000 (PEG6000).

18. The product according to any one of claims 1 to 9 or the method according to any one of claims 10 to 15, characterized in that The biodegradable biobased polymers and / or plasticizers are compounds that have passed the OECD TG 301B, C, D, F and 310 screening tests for a duration of up to 60 days in accordance with the Opinion (Risk Assessment Committee (RAC), Socio-Economic Analysis Committee (SEAC)) in the annex to the background document on Annex XV dossier of December 2020 on restriction of intentionally added microplastics, and are natural polymers or natural polymers that have not been chemically modified.

19. Use of a product as claimed in any one of claims 1 to 9 or 16 to 18 or a product prepared by a process as claimed in any one of claims 10 to 15 or 16 to 18 for controlled release of nutrients in agriculture, preferably in turf, crop cultivation, greenhouse cultivation and / or ornamental horticulture.

Citation Information

Patent Citations

  • CONTINUOUS METHOD FOR THE PRECIPITATION OF LIGNIN FROM BLACK LIQUOR

    FI20106073A

Cited By

  • Modified compound fertilizer and preparation method thereof

    CN121005598A